Siasat Difabel Melawan Diskriminasi Di Ranah Formal; Praktek Kebijakan Sekoleh Inklusi Di Yogyakarta - Pratiwi, Pratiwi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2012)
The objective of this research is to study learning process in inclusion education and discrimination behavior against disabled students in SMA Pembangunan Yogyakarta as a kind of inclusion school. The main spirit of inclusion education process is awareness of tolerance over existence reality. Inclusion school was begun by disabled people movement as a main catalyst. SMA Pembangunan Yogyakarta is selected as a research object. Interview guide was used as technique to collect primary data. Interview was conducted with all subjects in inclusion school such as course teachers, special advisor teacher, students, and high school principal. The result of this research indicated that learning process modification decrease discrimination. There are some education policies such as standard score for national final examination, standard curriculum, and limited access to entry inclusion school for mental retardation that contradicts with inclusion spirit. In other side, there were teachers caring disabled students, involving disabled students and take maximal efforts to teach different students, so their academic achievement is more optimum and discrimination against disabled student decrease. There are some kind of power that may support inclusion school existence such as modification curriculum technique, need of achievement from disabled students and consistent struggle from the main catalyst of inclusive school.